Advanced learners’ foreign language-related emotions across the four skills - Piniel, Katalin; Albert, Ágnes (Studies in Second Language Learning and Teaching, 2018)
Individual differences researchers have recently begun to investigate the concept of emotions and their role in language learning (MacIntyre, Gregersen, & Mercer, 2016). Our aim is to report on a project exploring English majors’ feelings related to their use of foreign languages. Using a qualitative research design, participants were asked to write a paragraph in their mother tongue (Hungarian) describing their emotional experiences in connection with foreign languages and one of the four language skills. Our database comprised altogether 166 paragraphs from 31 male and 135 female students, with 43 texts on listening, 35 on speaking, 47 on reading, and 41 on writing. With the help of content analytical techniques, the texts were divided into thematic units and coded by the two authors. A framework of academically-relevant emotions (Pekrun, 2014) was used to guide our initial coding and the categories were modified where it was felt necessary. Results indicate that the two emotions most frequently experienced by English majors are predominantly related to enjoyment and language anxiety, and these emotions vary not only according to the skill involved but also depending on the context of language use (in class or outside class).